2007
DOI: 10.1111/j.1742-4658.2007.05909.x
|View full text |Cite
|
Sign up to set email alerts
|

The hepoxilin connection in the epidermis

Abstract: The recent convergence of genetic and biochemical evidence on the activities of lipoxygenase (LOX) enzymes has implicated the production of hepoxilin derivatives (fatty acid epoxyalcohols) in the pathways leading to formation of the water‐impermeable barrier of the outer epidermis. The enzymes 12R‐LOX and eLOX3 are mutated in a rare form of congenital ichthyosis, and, in vitro, the two enzymes function together to convert arachidonic acid to a specific hepoxilin. Taken together, these lines of evidence suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 66 publications
1
63
0
2
Order By: Relevance
“…The concentration label in this study refers to the Sigma enzyme assuming 80% purity of the preparation. H 2 18 O (ϳ95%) was purchased 25 years ago from the Monsanto Research Corp. (Miamiburg, OH).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration label in this study refers to the Sigma enzyme assuming 80% purity of the preparation. H 2 18 O (ϳ95%) was purchased 25 years ago from the Monsanto Research Corp. (Miamiburg, OH).…”
Section: Methodsmentioning
confidence: 99%
“…Widely expressed in animals and plants, and also in some bacteria and fungi, LOX enzymes participate in diverse physiological and pathological processes. Mammalian 12R-LOX and epidermal lipoxygenase-3 (eLOX3), for example, play an indispensable role in skin barrier formation (2,3), whereas plant LOX enzymes are involved in stress responses and development (4). A distinctive characteristic of LOX enzymes in general is that the resting enzyme requires activation before catalytic reactions with fatty acids and molecular oxygen can begin (5)(6)(7).…”
Section: Lipoxygenases (Lox)mentioning
confidence: 99%
See 1 more Smart Citation
“…3). This is different in chemistry from synthesis of the group of epoxyhydroxy products that are often termed hepoxilins (28). Mechanistically, the epoxidation of the double bond could be accounted for by cross-molecular reaction of a peroxyl radical with a double bond (27).…”
Section: New Insights From Novel Products: Evidence For Intermoleculamentioning
confidence: 99%
“…ALOX12B and ALOXE3 encode for arachidonate 12(R)-lipoxygenase and arachidonate lipoxygenase-3, respectively. The protein product of CYP4F22, a cytochrome P450 protein, and the two lipoxygenases arachidonate 12(R)-lipoxygenase and arachidonate lipoxygenase-3 are part of the lipid metabolism pathway involved in the formation of o-hydroxyceramides from arachidonic acid [Brash et al, 2007]. ABCA12 (MIM] 607800) missense mutations leading to defects in the ATP-binding cassette were reported in LI cases (type 2 LI [MIM] 601277]) [Lefèvre et al, 2003] and ABCA12 truncation mutations were reported underlying HI patients Kelsell et al, 2005].…”
Section: Introductionmentioning
confidence: 99%